Pulmonary arterial hypertension screening practices in scleroderma patients among Canadian rheumatologists. Issue 3 (October 2020) - Quinn, Ryan; Koh, Deborah; Kelly, Dylan; Beattie, Karen A.; Larché, Maggie J.
Background: Current international guidelines recommend annual screening for pulmonary arterial hypertension with transthoracic echocardiogram and pulmonary function testing in all patients with scleroderma (systemic sclerosis). Our objectives were to determine Canadian rheumatologists' screening practices for pulmonary arterial hypertension in patients with systemic sclerosis and identify reasons why current guideline recommendations may not be followed. Methods: A survey was emailed to all Canadian Rheumatology Association members. They self-identified as systemic sclerosis experts or non-experts and provided basic demographic data. Participants were asked how frequently they screened with transthoracic echocardiogram and pulmonary function testing and, if applicable, why they did not adhere to recommendations. Results: A total of 71 rheumatologists participated, of whom 43 identified as non-experts. Overall, 81.4% ordered annual transthoracic echocardiogram and 77.6% annual pulmonary function testing. Rates of annual transthoracic echocardiogram testing were similar between experts and non-experts, whereas experts ordered annual pulmonary function testing more often. Clinicians with a higher proportion of systemic sclerosis patients in their practice were more likely to follow guidelines. There was an inverse relationship between years in practice and adherence to screening guidelines. The most common reason for not following screening guidelines was disagreement with recommendations, followed by unfamiliarity with guidelines. Conclusions: Pulmonary arterial hypertension screening rates remain sub-optimal in Canada but have improved since 2012. Failure to adopt guidelines is due to rheumatologists disagreeing with or not knowing current recommendations. Future studies should examine why rheumatologists disagree with guidelines and how to improve awareness.